Shadows of Sherwood - Magoon, Kekla (Magoon, Kekla. Robyn Hoodlum adventure., 2016)
Robyn Loxley's parents disappear one night, leaving her to fend for herself in Nott City. When Ignomus Crown takes over the city, Robyn must flee for her life, taking up with a band of teens with unique talents for evading problems. Robyn enlists their help to track down her parents and take back the city from Crown.